FEATURES OF THE ORGANIZATION AND CONDUCT OF INTERNATIONAL ASSESSMENT PROGRAMS - Ibadullaev, Kakhramon (Журнал иностранных языков и лингвистики, 2022)
This article analyzes the features of the organization and implementation of international assessment programs and innovative teaching methods that affect the improvement of education in research conducted by international assessment programs, the advantages of the education system of developed countries, as well as factors that lead to the decline of education. The task of educating a creative, independent thinker is primarily carried out in the national education system. This, in turn, requires a fundamental reform of the education system based on international standards. An excellent and competitive education system to international standards determines the future intellectual opportunities and development of our country. In the education of our republic, researches are being conducted on the issues of improving the educational system based on innovative technologies, strengthening its national ground, raising the training of socially active, competitive personnel to the level of world standards. Quality changes and high efficiency in the field of education depend on their compatibility with global educational requirements, the success of general secondary education students by participating in international assessment programs, first of all, on the extent to which their acquired competences are put into practice. PISA, PIRLS, EGMA, EGRA, TALIS, TIMSS programs that assess the quality of education are projects aimed at determining the level of knowledge of students in general education subjects.